Detection of subsurface meltwater in East Antarctica using SAR Interferometry - Li, Weiran (author) (2018)
Climate change has been a heated topic in recent years, and the mass loss of ice sheets is one aspect of it. The Antarctic Ice Sheet has experienced certain mass loss in the form of ice-shelf collapse and (sub-)surface melting, but thorough study remains limited due to the remote location of the continent. Therefore, remote sensing is expected to provide valuable information on Antarctica, in order to monitor its mass balance and gain insights on the extent of climate change. As one of the factors to the mass loss in Antarctica, subsurface melt can be critical yet hard to capture. The limitation of remote sensing data, especially valid optical images over polar regions may add to the issue. This study aims to exploit the potentiality of SAR Interferometry in detecting subsurface melt, as the microwave bands are not affected by weather and illumination, and the interferometric data may provide supportive information reflecting the properties of the physical environment. It is expected that by using this technique, the gap can be filled in when optical images are not available, or pure SAR images are not informative. The technique is applied to two ice shelves in East Antarctica, Roi Baudouin Ice Shelf and Amery Ice Shelf. And this study is expected to be operated over a broader scale such as the Antarctic continent and Greenland. Geomatics